A herbaceous species provides insights into drought-driven plant adaptation. (4th February 2023) - Johnson, Kate M; Fletcher, Leila R
Abstract : This article comments on: Thonglim A, Bortolami G, Delzon S, Larter M, Offringa R, Keurentjes JJB, Smets E, Balazadeh S, Lens F . 2023. Drought response in Arabidopsis displays synergistic coordination between stems and leaves. Journal of Experimental Botany 74, 1004–1021